Prevalence, patterns and associated factors of occupational eye injuries among patients attending National Eye Hospital, Colombo - Niluka Jeewanthi Gunathilaka; Dulani Lakmali Samaranayake (College of Community Physicians of Sri Lanka, 2022)
Introduction: Occupational eye injuries (OEIs) cause substantial morbidity, disability and economic loss globally. Local studies on OEIs and their prevention are scarce.   Objectives: To describe socio-demographic, occupational, clinical characteristics and associated factors among patients presenting with OEIs to National Eye Hospital, Colombo and their practices on prevention and first aid on OEI   Methods: A descriptive cross-sectional study was conducted in 218 consecutive patients presenting with OEIs to National Eye Hospital, Colombo. Data were collected using an interviewer-administered questionnaire and clinicalrecords. Practices on prevention and first aid were assessed and separate total scores were calculated.   Results: Of the 218 participants, majority were males (n=213; 97.7%) with mean age of 34 years (SD=11.5). Most of them were married (65.6%) as well as the sole bread winners (58.3%). Most affected were welders (29.8%) and construction workers (19.7%). Flying-particles (41.7%), grinding-particles (36.7%) and chemicals (11%) were main causes, resulting in 57.3% foreign bodies, 10.1% abrasions and 5.9% chemical-burns. Thirteen (6%) injuries were bilateral, 18 (8.7%) had partial/complete vision loss and 121 (55.5%) were recurrent. Majority had goggles (90.7%), spectacles (60.8%), hand-shields (64.1%) but not face-masks (9.4%) or welding-helmets (32.4%. Personnel protective equipment (PPE) usage was compulsory in 63.3% workplaces but only 16.5% used PPE during injury, reasons being unavailability (22.5%) and low priority (20.6%). The PPE use was significantly (p=0.004) higher in settings where it was compulsory.   Conclusions & Recommendations: The OEI were common among young male workers and in some occupations. Availability and utilization of PPE was poor and overall practices in first aid were unsatisfactory. Legislation, provision of PPE and worker education targeting a behaviour change on prevention and first aid are recommended.